To Examine How Task-Based Language Teaching May Improve Sixth-Grade Students’ Speaking Skills in a Public Institution in La Ceja (2023)
ABSTRACT : This action research intended to determine to what extent using a Task-Based Language Teaching Approach allowed improving students’ speaking skills. This project was performed in an urban institution in La Ceja, Antioquia, with 6th graders. The actions executed were centered on a task cycle composed of pre-task, task-cycle, and language focus, and all these stages were concentrated on the speaking skill. Data instruments were journals, a checklist, some recordings, and a questionnaire. Four main findings were exposed in the following names: the relevance of developing tasks and topics in TBLT to improve learners’ speaking skills, the teacher’s role: promoting a student-centered class through actions and support in TBLT, the students' role in TBLT: active participation and attitudes toward tasks, and the speaking skills development: increasing performance and awareness of thew own process.